2007
DOI: 10.1158/1535-7163.mct-07-0001
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin enhances TRAIL-mediated apoptosis in colon cancer cells by inducing the accumulation of death receptors in lipid rafts

Abstract: Cytokines such as tumor necrosis factor-related apoptosisinducing ligand (TRAIL) can induce apoptosis in colon cancer cells through engagement of death receptors. Nevertheless, evading apoptosis induced by anticancer drugs characterizes many types of cancers. This results in the need for combination therapy. In this study, we have investigated whether the flavonoid quercetin could sensitize human colon adenocarcinoma cell lines to TRAIL-induced apoptosis. We report that quercetin enhanced TRAILinduced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 37 publications
7
104
0
Order By: Relevance
“…In addition, quercetin increases apoptosis by altering anti-apoptotic proteins, which supports our fining that FEOJ suppressed an anti-apoptotic factor Bcl-2, and X-IAP in U937 cells. Regarding cIAP-1, our data showed that FEOJ did not influence the expression of cIAP-1 which is consistent with previous reports showing that quercetin treatment did not affect the levels of cIAP-1 (Psahoulia et al, 2007;Kim et al, 2008). In previous studies, quercetin also leads to reduction in MMP (ΔΨm), and subsequent activation of caspases, thus ultimately inducing apoptosis via the intrinsic pathway in several types of cancer cells (Mouria et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, quercetin increases apoptosis by altering anti-apoptotic proteins, which supports our fining that FEOJ suppressed an anti-apoptotic factor Bcl-2, and X-IAP in U937 cells. Regarding cIAP-1, our data showed that FEOJ did not influence the expression of cIAP-1 which is consistent with previous reports showing that quercetin treatment did not affect the levels of cIAP-1 (Psahoulia et al, 2007;Kim et al, 2008). In previous studies, quercetin also leads to reduction in MMP (ΔΨm), and subsequent activation of caspases, thus ultimately inducing apoptosis via the intrinsic pathway in several types of cancer cells (Mouria et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports demonstrated that quercetin induced apoptosis in several types of cancer cells (Psahoulia et al, 2007), and it augmented apoptosis by up-regulating DR5 expression (Jang et al, 2003). These findings are consistent with our results even though we did not demonstrate the up-regulation of DR5 by FEOJ in that FEOJ also induced caspase 8 activation.…”
Section: Discussionsupporting
confidence: 91%
“…2) enhances TRAIL-induced apoptosis by causing the redistribution of DR4 and DR5 into lipid rafts in colon cancer cells. 143 The COX-2 inhibitor DuP-697 does not modulate the levels of DR5 and DR4 although it enhances TRAIL-induced apoptosis in cancer cells. Instead, it sensitizes cells to TRAIL-induced apoptosis by inducing clustering of DR5 at the cell surface and the redistribution of the death-inducing signaling complex components (DR5, FADD, and procaspase-8) into lipid rafts.…”
Section: Induction Of Death Receptor Redistribution and Clustering Bymentioning
confidence: 99%
“…The bioactivities of quercetin are complex and include antioxidative, antiviral, antibacterial and anti-inflammatory effects (4,6,7). Recently, quercetin was found to possess strong anticancer properties in colon cancer (8)(9)(10)(11), breast cancer (12,13), leukemia (14)(15)(16), hepatocellular carcinoma (17), pancreatic carcinoma (18), salivary adenoid cystic carcinoma (19) and lung cancer (20). Although the anti-tumor effects of quercetin have been examined in several tumors, very little is known about its effects in osteosarcoma cells.…”
Section: Introductionmentioning
confidence: 99%